Catalisadores de Mo suportados sobre sílica, sílica-titânia ou sílica-zircônia promovidos por Co ou Ni: avaliação do método de preparação e da composição do suporte na atividade para HDS - Silva Neto, Alano Vieira da (2012)
Hydrodesulfurization (HDS) catalysts containing Mo, NiMo or CoMo were supported on silica, silica-titania and silica-zirconia. These supports were synthesized by the sol-gel method, using citric acid as an agent to pore formation and to complex Ti and Zr. The incorporation of the precursor salts of the active phases was done during the sol-gel preparation of the different supports (in situ addition) or by impregnation using citric acid as chelating agent. The catalysts in the oxide form were characterized by atomic absorption spectroscopy (AAS), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), temperature-programmed desorption of NH3 (TPD-NH3), Fourier Transform infrared spectroscopy (FTIR), thermogravimetric (TG) and differential thermal analysis (DTA), N2 adsorption/desorption, diffuse reflectance UVVis spectroscopy (DRSUV-Vis), temperature-programmed reduction with H2 (TPR-H2) and evaluated from 240 to 300°C in the HDS of thiophene used a model molecule. Supports and catalysts showed high specific surface area and pore volume as result of the use of citric acid in the preparation of the respective sol-gel mixtures. From XRD data was evident that the citric acid promoted a high dispersion of Ti and Zr in the silica framework, because was not observed XRD peaks related to separated phases of those metals. The XRD patterns of the catalysts did not show diffraction peaks related to other species or oxides of Mo, Co or Ni, behavior that was attributed to the high dispersion of these metal species in the different supports that was confirmed by DRSUV-Vis and H2-TPR. The HDS reaction of thiophene on NiMo and CoMo catalysts showed a higher activity for the first ones, which were more active when supported on silica or silica-zirconia. This result was attributed to the higher interaction of Ni with Mo, which generated a higher degree of reducibility of the Mo species, facilitating the subsequent sulphidation process and consequently favoring the formation of the NiMoS phase, which is indicated as the main responsible of the catalyst activity in the HDS process. The lower activity of the catalysts supported in situ on SiO2-TiO2, was related to the formation of separated phases of Mo and Ni or Co sulfides, which are less active to the HDS reaction.